2021
DOI: 10.1080/14992027.2020.1864486
|View full text |Cite
|
Sign up to set email alerts
|

Development of a public audiology service in Southern Malawi: profile of patients across two years

Abstract: Objective: To describe the profile of patients attending the Queen Elizabeth Central Hospital (QECH) audiology clinic in Malawi, over a two-year period (2016)(2017). Design: A retrospective patient record review.Study sample: There were 2299 patients assessed at the QECH audiology department between January 2016 to December 2017. Adult patients' ages ranged from 18 to 94 years (M = 45.8, SD = 19.22). The mean age of children included in this study was 7.7 years(SD= 5.21). Overall, 45.4% of patients were female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The results, from this Malawian population, found that the LoCHAid and the refurbished programmed hearing aids were similarly beneficial for people with high frequency hearing loss but that some improvements are required to improve the LoCHAid sound quality and user experience. Low hearing aid uptake or hearing aid availability in Sub Saharan Africa has been noted in the literature (Hlayisi & Ramma, 2019;Parmar et al, 2021). Furthermore, many countries rely on hearing aid donations from non-governmental organisations (Seelman & Werner, 2014;Thiga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results, from this Malawian population, found that the LoCHAid and the refurbished programmed hearing aids were similarly beneficial for people with high frequency hearing loss but that some improvements are required to improve the LoCHAid sound quality and user experience. Low hearing aid uptake or hearing aid availability in Sub Saharan Africa has been noted in the literature (Hlayisi & Ramma, 2019;Parmar et al, 2021). Furthermore, many countries rely on hearing aid donations from non-governmental organisations (Seelman & Werner, 2014;Thiga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Low hearing aid uptake or hearing aid availability in Sub Saharan Africa has been noted in the literature (Hlayisi & Ramma, 2019; Parmar et al, 2021). Furthermore, many countries rely on hearing aid donations from non-governmental organisations (Seelman & Werner, 2014; Thiga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) Only behind-the-ear (BTE) HAs are refurbished; in-the-ear (ITE) HAs are only used for spare parts. Parmar et al [ 52 ] UK, Malawi Descriptive, Cross sectional, Retrospective Not mentioned 2299 patients, 1521 adults (age: M = 45.8, SD = 19.2) and 778 children (age: M = 7.7, SD = 5.2) Description of an audiology clinic in Malawi, developed with the help of Sound Seekers, now Deaf Kidz International. Refurbished HAs come from a Zambia lab.…”
Section: Table A1mentioning
confidence: 99%